Percepção de assistentes sociais e de profissionais que atuam na equipe de saúde da família sobre o papel do serviço social - Garcia, Elinausa Lisboa dos Santos (2020)
This work was developed with the objective of understanding the perception of social workers and health professionals who are part of the Family Health team about the role of the social worker in the Family Health Strategy. Considering that the FHS is the main gateway to the health system, the research focused on answering how the perception of health professionals in relation to the role of the Social Worker in the FHS impacts on their praxis and on the way of establishing interactions in the work process, so that the understanding of the practice connected to the theory contributes to a better performance of the professional, in the service to the users of the health system. The study has an exploratory descriptive aspect, developed through the quantitative and qualitative approach. Participated in the research social workers and health professionals who work in the Basic Family Health Units and make up the Family Health team in the FHS: doctors, nurses, technicians and / or nursing assistants and Community Health Agents Saúde, in the city of Uberlândia-MG. In order to achieve both the objectives referred to above and those described in the research, for the quantitative method, data collection was carried out through a self-administered questionnaire with professionals from the Family Health teams of the Basic Family Health Units; and for the qualitative method, interviews with semi - structured script and focus group with social workers were used. The results showed that even though they are aware of the contribution of the Social Service professional to the team, a considerable number of professionals from the family health team have difficulty understanding the dimension of the role of the social worker. Also presented relevant information for the knowledge of the trajectory of the social service in the SMS of Uberlândia and how the social worker works in social occupational spaces such as the Integrated Health Care Unit, the Basic Health Unit and the Basic Family Health Unit. , in addition to show that the social situation, the working conditions and their form of organization, can contribute to the physical and mental strain affecting the health of these workers.